A Review of Hybrid Three-Level ANPC Inverters: Topologies, Comparison, Challenges and Improvements in Applications - Xiaobin Mu; Hao Chen; Xiang Wang; Weimin Wu; Houqing Wang; Liang Yuan; Henry Shu-Hung Chung; Frede Blaabjerg (Energies)
Considering the cost, efficiency, power density, and other issues of the power electronic system, many papers have mixed the wide-bandgap (WBG) power devices, mainly SiC MOSFET and GaN FET/HEMT, with Si IGBT/MOSFET in the three-level active neutral-point clamped (T-ANPC) topology, forming the hybrid T-ANPC (HT-ANPC) topology. This paper reviews these latest HT-ANPC topologies from the perspective of the material types of switching devices and compares the advantages and disadvantages of various topologies. The potential challenges of HT-ANPC inverters in several mainstream applications are reviewed, and their improvements are compared and discussed in detail. Next, a brief topology selection and design process are provided based on analyzing various typical topologies. In addition, some future research trends on this topic are discussed. The paper will help researchers to select appropriate HT-ANPC topologies in different applications and have a better understanding of the critical issues to be considered during system design.